OBTAINMENT OF HYBRID COMPOSITES BASED ON HYDROGEL AND PORTLAND CEMENT - Santos, Jefferson C. dos [UNESP]; Tashima, Mauro M. [UNESP]; Moura, Marcia R. de [UNESP]; Aouada, Fauze A. [UNESP] (Soc Brasileira Quimica, 2016)
In this study, a novel hybrid composite based on biodegradable hydrogel and Portland cement with promising technological properties was reported. In the first step, a full 2(3) with central point factorial design was utilized to obtain the enhanced polyacrylamide-carboxymethylcellulose hydrogel compositions. A mathematical model was devised, indicating that the 3 main variables were significant and the AAm and MBAAm variables positively contributed to the mode and showing that the CMC variable had the opposite contribution. In the second step, these compositions were mixed with Portland cement to obtain the hybrid composites. The presence of cement improved the mechanical properties of polymeric matrices, and electronic microscopic micrographics revealed that the hydrogels were well adhered to the cement phase and no phase separation between hydrogel and cement was detected. Finally, using the energy dispersive X-ray technique, the elements Na, Mg, Al, Si, S, K, Ca and Fe were detected in the polymeric matrix, consistent with the hybrid composite formation.
Keywords: factorial design; hybrid composites; hydrogel; Portland cement; mechanical property